Judicial Decisions in Cases Involving the Liability of Professional Attorneys - Raczyński, Aleksander (Studia Oeconomica Posnaniensia, 2015)
This paper presents the body of case law concerning the civil liability of professional legal advisors (barristers and solicitors). The author analysis court decisions regarding the conditions of civil liability for the aforementioned professionals - tort, injury, and causation. In the conclusions the author presents the difficulties associated with proving the existence of civil liability in this occupational group.